Are stock market returns driven by foreign exchange rate movements in frontier markets? Evidence from the Colombo Stock Exchange - Balapatabendi, Sanjana Devin (2021)
According to financial theory, a change in exchange rates should affect the value of a firm. However, prior research shows mixed evidence regarding the relationship between stock prices and exchange rates and existing literature primarily focusses on developed and emerging markets while frontier markets have received little research attention. This study extends previous research around foreign exchange exposure by examining the relationship contemporaneous changes in exchange rates and their lags have on stock returns at both the market and industry level. This study also examines the relationship under two different assumptions: an assumption of symmetric impacts and an assumption of asymmetric impacts. The analysis uses data from 262 companies listed on the Colombo Stock Exchange and is conducted over the period from 2012 to 2021 and over three subperiods to examine the changes in the relationship over time.